2016
DOI: 10.1371/journal.pone.0154927
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Visual Field Representations in the Visual Wulst of a Laterally Eyed Bird, the Zebra Finch (Taeniopygia guttata)

Abstract: The visual wulst is the telencephalic target of the avian thalamofugal visual system. It contains several retinotopically organised representations of the contralateral visual field. We used optical imaging of intrinsic signals, electrophysiological recordings, and retrograde tracing with two fluorescent tracers to evaluate properties of these representations in the zebra finch, a songbird with laterally placed eyes. Our experiments revealed that there is some variability of the neuronal maps between individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 67 publications
0
11
0
1
Order By: Relevance
“…The visual Wulst is likely homologous with V1 and displays some similarities in laterally eyed birds. These include orientated edge detectors ( Ng et al, 2010 ), flexible reward and stimulus association coding ( Anderson et al, 2020 ), and retinotopically organized maps of visual space ( Revzin, 1969 ; Gusel’nikov et al, 1977 ; Bischoff et al, 2016 ). There is also evidence that the Wulst is involved in representing global spatial information in comparison with the tectofugal pathway, as opposed to local beacons.…”
Section: What Happens When a Pigeon Looks At A Distant Object Lateral...mentioning
confidence: 99%
“…The visual Wulst is likely homologous with V1 and displays some similarities in laterally eyed birds. These include orientated edge detectors ( Ng et al, 2010 ), flexible reward and stimulus association coding ( Anderson et al, 2020 ), and retinotopically organized maps of visual space ( Revzin, 1969 ; Gusel’nikov et al, 1977 ; Bischoff et al, 2016 ). There is also evidence that the Wulst is involved in representing global spatial information in comparison with the tectofugal pathway, as opposed to local beacons.…”
Section: What Happens When a Pigeon Looks At A Distant Object Lateral...mentioning
confidence: 99%
“…In addition, they showed that eye alignment as well as binocularity and retinal disparity tuning in the Wulst, depend on early binocular experience, as they do in mammals (Pettigrew & Konishi, ). Subsequent studies show that the Wulst contains several retinotopic areas, each with distinct thalamo‐Wulst inputs and functional properties (Bischof et al, ). In one area, >90% of neurons respond to illusory contours (contours inferred from boundaries of phase‐shifted gratings), as do a subset of neurons in the mammalian V1 (Nieder & Wagner, ).…”
Section: Visual Processing In Birdsmentioning
confidence: 99%
“…Visual Wulst sends projections to various structures including the hippocampal formation and the nido-and mesopallium (Shanahan et al 2013;Atoji et al 2018). The visual Wulst contains many visually responsive neurons (Revzin 1969;Gusel'nikov et al 1977;Ng et al 2010), which are organised according to multiple retinotopic maps (Michael et al 2015;Bischof et al 2016) and are sensitive to motion and orientation akin to those found in the mammalian visual cortex. Visual Wulst also shows column-like organisation (Stacho et al 2020).…”
Section: Introductionmentioning
confidence: 99%